Developing Teaching Instructions through the Practice of Lesson Study in Teaching Passive Voice - Imelda Mallipa; Riana Murianty (Linguistic, English Education and Art (LEEA) Journal, 2020)
Conducting a study to find the best practices in teaching a topic through lesson study procedures provided insight about what to do in planning a lesson and how students learn in a set context. The present study offered strategies in teaching passive voice and explanations about how to deal with some problems in teaching this problematic topic. This study was conducted by following the steps of lesson study and obtained the data from pretest, the notes taken in planning, doing and reflecting. The participants were 40 English Education students at Universitas Papua. The results showed that the possible strategy in teaching passive voice was using text to discuss grammar. Before deciding to use a text, teachers should check the knowledge of students in grammar and students’ prior knowledge of topic in text. In teaching process, drawing students’ attention to the grammatical contsructions, the agent or the recipient of the action should be done after discussing the main idea and information in text in order to understand and use grammar in context. Keywords: Teaching Instructions, Lesson Study, Passive Voice